(untitled) (Tempo e Argumento, 2009)
The present article addresses the relationship among media, memory and forgetfulness in contemporary society. The central point is a reflection on how media resources act to produce events and meanings about the past, considering it is fundamental to reflect on the influence of such resources in the historical production of the present time itself.